The Non-linearity of the Relationship between Human Capital and Exports in Brazil - evidences of regional differences - Gilberto Fraga; Carlos Bacha (European Regional Science Association (ERSA), 2011)
The study of Brazilian export determinants is a very important issue to policy-markers, principally when the export determinants are different among the Brazilian states or regions. Human capital (measured by the average level of employee formal schooling) has been one of these determinants and this paper, basing on Dixit and Woodland (1982) model, aims to evaluate the role played by human capital in the evolution of Brazilian states exports from 1995 to 2006, highlighting the differences among Brazilian states and/or regions. The empirical analysis is implemented by running regression of the data organized into a panel and considering the fixed effects (i.e., the amenities) among the 27 Brazilian states. The findings are consistent with the selected theoretical model and suggest that human capital has a non-linear effect on exports. The latter suggests the continuous improvement in the worker skill should not be neglected by public policies aimed at increasing the foreign trade of Brazilian states, but the unique characteristics of these states must be taken into account.
Keywords: 330